Postflight Data Processing Instructions on the Use of Unmanned Aerial Vehicles (UAVs) for Agricultural Applications - Sri Charan Kakarla; Yiannis Ampatzidis (EDIS, 2019)
Remote sensing applications for agriculture often require periodically collected high-resolution data, which are difficult to obtain by manned flights or satellite imagery. This 6-page document provides guidance on the use of post-processing software to visualize data collected by unmanned aerial vehicles (UAVs) for agricultural applications. It provides step-by-step instructions for using the data collected from a UAV flight to create several types of maps and indices. Written by Sri Charan Kakarla and Yiannis Ampatzidis, and published by the UF/IFAS Department of Agricultural and Biological Engineering, October 2019.